On Approximation of Laplacian Eigenproblem over a Regular Hexagon with Zero Boundary Conditions (Journal of Computational Mathematics, 2004)
In my earlier paper [4], an eigen-decompositions of the Laplacian operator is given on a unit regular hexagon with periodic boundary conditions. Since an exact decomposition with Dirichlet boundary conditions has not been explored in terms of any elementary form. In this paper, we investigate an approximate eigen-decomposition. The function space, corresponding all eigenfunction, have been decomposed into four orthogonal subspaces. Estimations of the first eight smallest eigenvalues and related orthogonal functions are given. In particular, we obtain an approximate value of the smallest eigenvalue $λ_1$～$\frac{29}{40} π^2=7.1555$, the absolute error is less than 0.0001.
Keywords: Laplacian eigen-decomposition; Regular hexagon domain; Dirichlet boundary conditions.